2019
DOI: 10.3390/molecules24193542
|View full text |Cite
|
Sign up to set email alerts
|

Biological Effects of Shikonin in Human Gingival Fibroblasts via ERK 1/2 Signaling Pathway

Abstract: Shikonin, an active ingredient of Lithospermum erythrorhizon, exerts anti-inflammatory and antibacterial effects, and promotes wound healing. We investigated whether shikonin stimulated gingival tissue wound healing in human gingival fibroblasts (hGF). In addition, we evaluated the effects of shikonin on the mitogen-activated protein kinase (MAPK) signaling pathway, which has an important role in wound healing. hGF were subjected to primary culture using gingiva collected from patients. The cells were exposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 44 publications
(52 reference statements)
0
21
0
Order By: Relevance
“…For A/S concentration of 1 wt.% suppression of cell motility was observed, as already witnessed by confocal microscopy analysis. In previous studies, where pure A/S compounds were tested (contained in low amounts in the A/S mixture that we applied in the scaffolds), it was found that shikonin (at 1 μΜ) and deoxy-shikonin (at 1.5 and 3 μΜ) enhanced the in vitro migration of human gingival fibroblasts and keratinocytes, respectively [ 39 , 40 ]. Added to that, shikonin and alkannin succeeded in accelerating (dose-dependently) the proliferation of granuloma tissue in Wistar rats with the same potency, therefore, suggesting that the absolute configuration of the hydroxyl group in the side chain of these molecules did not seem to play any important role on producing this accelerating effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For A/S concentration of 1 wt.% suppression of cell motility was observed, as already witnessed by confocal microscopy analysis. In previous studies, where pure A/S compounds were tested (contained in low amounts in the A/S mixture that we applied in the scaffolds), it was found that shikonin (at 1 μΜ) and deoxy-shikonin (at 1.5 and 3 μΜ) enhanced the in vitro migration of human gingival fibroblasts and keratinocytes, respectively [ 39 , 40 ]. Added to that, shikonin and alkannin succeeded in accelerating (dose-dependently) the proliferation of granuloma tissue in Wistar rats with the same potency, therefore, suggesting that the absolute configuration of the hydroxyl group in the side chain of these molecules did not seem to play any important role on producing this accelerating effect.…”
Section: Discussionmentioning
confidence: 99%
“…Another group has reported that shikonin and alkannin showed non-selective toxicity towards normal cell lines (human skin fibroblasts), with the IC 50 values being 1.2 ± 0.1 μM and 1.5 ± 0.1 μM, respectively [ 42 ]. It had also been mentioned that a commercial sample of shikonin and lithospermi radix extract induced the proliferation of human fibroblasts [ 39 , 43 ]. The highest proliferation rate of Hs27 fibroblasts was achieved at day 3 by isovaleryl-shikonin (at 500 nM and 1 μM) and dimeric A/S (at 1 μM).…”
Section: Discussionmentioning
confidence: 99%
“…Future efforts towards uncovering the anti-inflammatory potential of shikonin may prove significant. Further promoting the importance of future investigations, shikonin has shown significant promise as an antimicrobial and antiviral agent, as well as a wound healing promoter [ 224 , 229 , 237 , 238 , 239 , 240 , 241 , 242 ] ( Figure 4 B ). Nevertheless, it remains to be determined whether these beneficial properties of shikonin are mediated through modulation of PKM2 activity.…”
Section: Emerging Areas Of Research Involving Pkm2mentioning
confidence: 99%
“…Shiunko ointment is a traditional botanic formula used for treatment of wounded skin without causing undesirable side effects in China and Japan (Higaki et al, 1999), and it has been found to accelerate the epithelization of wounded skin infected with P. aeruginosa (Huang et al, 2004). The mechanisms underlying the Shiunkomodulated epithelization possibly being through enhancing fibroblast proliferation and collagen production, and suppressing skin inflammation (Yan et al, 2015;Imai et al, 2019). In addition to inhibition of P. aeruginosa QS and biofilm formation, Qi Gui Yin decoction (9.9 g for every kg of body weight) was also identified to promote host immune response to P. aeruginosa infections by enhancing the antibody reactivity to β-lactamases, including VIM-1, SPM-1, and TEM-1, and manifested anti-inflammatory effects by reducing the levels of IL-1β and Th1/Th2 ratio in a rat model of abdominal infection (Kong et al, 2015).…”
Section: Immunomodulationmentioning
confidence: 99%
“…Huang et al (2004);Yan et al (2015);Imai et al (2019) Qi Gui Yin Increase of B cell response and downregulation of inflammationEnhancement of antibody reactivity to β-lactamases and reduction of the levels of IL-1β and Th1/Th2 ratio Kong et al (2015) Qingre Baidu mixture Promotion of angiogenesis and wound healing Upregulation of the expression of HIF-1α, HIF-2α and VEGF Shan et al (2019) Frontiers in Pharmacology | www.frontiersin.org August 2021 | Volume 12 | Article 737252…”
mentioning
confidence: 99%